2013
DOI: 10.1016/j.jad.2013.06.051
|View full text |Cite
|
Sign up to set email alerts
|

In your eyes: Does theory of mind predict impaired life functioning in bipolar disorder?

Abstract: Background Deficits in emotion perception and social functioning are strongly implicated in bipolar disorder (BD). Examining theory of mind (ToM) may provide one potential mechanism to explain observed socio-emotional impairments in this disorder. The present study prospectively investigated the relationship between theory of mind performance and life functioning in individuals diagnosed with BD compared to unipolar depression and healthy control groups. Methods Theory of mind (ToM) performance was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
2
31
0
5
Order By: Relevance
“…If enhanced ToM decoding skills simply marked a transient dysphoric state, then both the past-depressed and never-depressed groups would show superior performance on the RMET after a sad mood induction than after a happy mood induction. In contrast to these results, Purcell et al [73] described a similar accuracy on the RMET in remitted individuals with unipolar depression as in controls.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…If enhanced ToM decoding skills simply marked a transient dysphoric state, then both the past-depressed and never-depressed groups would show superior performance on the RMET after a sad mood induction than after a happy mood induction. In contrast to these results, Purcell et al [73] described a similar accuracy on the RMET in remitted individuals with unipolar depression as in controls.…”
Section: Resultsmentioning
confidence: 67%
“…Studies investigating the reasoning aspect of ToM in dysphoria are lacking. Apart from Harkness et al [33,68,72], three other groups of researchers investigated ToM after symptom remission in MDD patients, one of which found no significant differences between patients and controls [73], a second one reported on continued but more moderate forms of ToM deficit after symptomatic remission [75], and a third one found that ToM deficits in these patients are associated with higher risk for relapse [74]. In order to get a clearer picture about ToM functioning during the remitted state of major depression, the number of longitudinal studies comparing ToM performance before and after recovery should be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Number of lifetime manic episodes (range = 1–99 6 , M = 11.38, SD = 20.25) and depressive episodes (range = 0–99, M = 14.39, SD = 23.05) were assessed in the participants diagnosed with BD disorder using the NIMH-LCMr. All participants then completed a series of procedures not relevant to the present study (for other articles discussing this dataset, see Gilbert, Nolen-Hoeksema, & Gruber, 2013; Gruber, Kogan, Mennin, & Murray, in press; Gruber, Purcell, Perna, & Mikels, 2013; Kang & Gruber, 2013; Purcell, Phillips, & Gruber, 2013). At the end of the session, participants completed the extreme valuing of happiness and general goal pursuit scales using an online survey.…”
Section: Methodsmentioning
confidence: 99%
“…Great variability has been observed among studies of social cognition in euthymic bipolar patients: while some of them revealed large magnitudes of impairment (Malhi et al, 2008;Montag et al, 2008) others reported small effect sizes (Martino et al, 2011;Lee et al, 2013) or the absence of patient-control differences (Caletti et al, 2013;Purcell et al, 2013). A preliminary meta-analysis (Samamé et al, 2012) revealed moderate-to-large effect sizes for theory of mind and small effect sizes for emotion recognition, favoring healthy controls.…”
Section: Introductionmentioning
confidence: 99%